2023
DOI: 10.1093/ijnp/pyad012
|View full text |Cite
|
Sign up to set email alerts
|

Redox and Immune Signaling in Schizophrenia: New Therapeutic Potential

Abstract: Redox biology and immune signaling play major roles in the body, including in brain function. A rapidly growing literature also suggests that redox and immune abnormalities are implicated in neuropsychiatric conditions such as schizophrenia, bipolar disorder, autism, and epilepsy. In this article we review this literature, its implications for the pathophysiology of schizophrenia, and the potential for development of novel treatment interventions targeting redox and immune signaling. Redox biology and immune s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 142 publications
(168 reference statements)
0
5
0
Order By: Relevance
“…This oxidative stress can also result in mitochondrial dysfunction, another potential factor in bipolar disorder ( 5 , 6 ). Redox homeostasis is crucial not only for containing tissue damage over time but also for maintaining appropriate signaling in specific biochemical pathways ( 81 ). Redox dysregulation is also notably regarded as a pivotal environmental risk factor in the neurodevelopmental context of schizophrenia ( 7 ).…”
Section: Dysfunctional Metabolism In Bipolar Disorder and Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…This oxidative stress can also result in mitochondrial dysfunction, another potential factor in bipolar disorder ( 5 , 6 ). Redox homeostasis is crucial not only for containing tissue damage over time but also for maintaining appropriate signaling in specific biochemical pathways ( 81 ). Redox dysregulation is also notably regarded as a pivotal environmental risk factor in the neurodevelopmental context of schizophrenia ( 7 ).…”
Section: Dysfunctional Metabolism In Bipolar Disorder and Schizophreniamentioning
confidence: 99%
“…Moreover, prolonged oxidative stress in the circuitry of neurotransmitters, e.g., parvalbumin interneurons in GABAergic circuits, have been identified in schizophrenia and bipolar disorder ( 84 86 ). This implies that redox dysregulation can be regarded as a notable environmental risk factor for neuronal dysfunction in psychiatric diseases which may relate to psychotic symptoms ( 5 , 7 , 81 ).…”
Section: Conclusion: Sleep Metabolism and Mental Health – Current Sta...mentioning
confidence: 99%
“…Consequently, the review by Dwir et al. (2023) underscores redox and immune signaling as critical therapeutic targets in schizophrenia ( 46 ).…”
Section: The Vulnerability-stress-inflammation Model Of Schizophreniamentioning
confidence: 99%
“…Williams et al (2022) identified a significant correlation between genetically determined IL-6 levels and gray matter volumes in the frontotemporal cortex of schizophrenia patients (45). Consequently, the review by Dwir et al (2023) underscores redox and immune signaling as critical therapeutic targets in schizophrenia (46).…”
Section: The Vulnerability-stressinflammation Model Of Schizophreniamentioning
confidence: 99%
“…Adolescence is a highly metabolically demanding period [ 18 ], rendering the brain potentially sensitive to the imbalance between antioxidant capacity and reactive oxygen species (ROS) leading to oxidative stress (OxS) [ 19 ]. Preclinical findings indicate increased vulnerability of the brain to redox dysregulation during peripuberty, compared to later developmental stages [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%